The impact of diet on systemic lupus erythematosus - a review article - Dąbrowska, Natalia; Kudas, Zuzanna; Nowocin, Paweł; Koszyk, Martyna; Litwin, Aleksandra; Krzywicka, Karolina; Kulczyński, Dawid Wiktor; Kumięga, Paulina; Perchel, Nikola; Wasiński, Piotr (Quality in Sport, 2024)
Introduction. Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting multiple organs and systems, with a complex pathogenesis involving genetic, hormonal, and environmental factors. The disease manifests with variable clinical features and can lead to significant morbidity and increased cardiovascular risk. Aim of Study. The aim of the study was to evaluate the role of diet and supplementation with specific nutrients in the management of SLE, focusing on omega-3 and omega-6 fatty acids, vitamin D, gut microbiota, and dietary patterns like low glycemic index and Mediterranean diets. Materials and methods. More than 30 articles addressing these issues were analyzed. They were found using the PubMed search engine, and the time frame of these publications covered the last 10 years. Results. Studies suggest that omega-3 supplementation, vitamin D, and synbiotics can reduce disease activity, inflammation, and fatigue in SLE patients. A balanced omega-6/omega-3 ratio, along with specific dietary patterns, improved cardiovascular function and reduced inflammation. The Mediterranean and low-GI diets also contributed to better disease control and quality of life. Conclusions. Dietary interventions discussed in the paper can be beneficial adjuncts to pharmacological treatments in SLE management. These changes may improve disease activity and overall well-being. Further long-term studies are needed to confirm these findings.